CHARACTERISTICS OF MANAGEMENT ACCOUNTING INFORMATION SYSTEMS, PARTICIPATION IN BUDGETING, BUSINESS STRATEGY AND ENVIRONMENTAL UNCERTAINTY ON MANAGERIAL PERFORMANCE - Soni Agus Irwandi; Agus Samekto; Reza Arlinda; Joicenda Nahumury; Velin Ivonialita; Idlal Awwalul Anisa (Sekolah Tinggi Ilmu Ekonomi DR KH EZ Mutaqien, 2022)
The purpose of this study was to determine the effect of management accounting information system characteristics, budgeting participation, business strategy on managerial performance with environmental uncertainty as a moderating variable. Quantitative research method using a questionnaire to obtain the data. The sample of this research is an active employee in administration and finance in each division of PT PJB Surabaya. The data analysis technique used in this study is moderating regression analyze. The results of the research inform that the characteristics of management accounting information systems, participatory budgeting and business strategy have a significant effect on this research. The research results also inform that environmental uncertainty strengthens the relationship between the influences of business strategy on managerial performance. The contribution of this research is useful for companies to increase the capacity of management information systems and flexible budgeting according to the needs and determination of company strategy.